Songs as Teaching Resources in the Young Learners' ESL Classroom - Gyða Hrund Þorvaldsdóttir (2008)
Grunnskólabraut Many schools in Iceland have started to teach English in the first grade, but they may lack appropriate material to make the most of these lessons. The English lessons that take place at such a young age are usually in the hands of the class teacher. If the teacher has not received training or insight into language teaching he or she might not have enough training to get the most out of the lesson. The teacher might also lack material that is specially aimed at this age group. In this case we are talking about children five to eight years old so I decided to write these songs in hope that they might become useful for the youngest learners and valuable tools for their class teachers so they can bring variety to the class and make the learning process an experience that is fun for everyone. Moreover, important language components like listening, pronunciation and vocabulary can easily be introduced through the music. Keywords: Songs, music, ESL.